A bibliometric analysis of global research on drinking water and health in low- and lower-middle-income countries. (22nd February 2023) - Bennett, Alexa; Demaine, Jeffrey; Dorea, Caetano; Cassivi, Alexandra
Abstract: Heightened interest in drinking water research in recent decades has been aimed at narrowing the knowledge gaps surrounding water and health in a global pursuit to provide safely managed drinking water services to populations who continue to lack access. This study used bibliometrics and network analysis to produce a global overview of publications and groups that have contributed to research on drinking water and health in low- and lower-middle-income countries (LLMICs). The United States and the United Kingdom, which have historically dominated the field based on the production and impact of scientific literature, remain at the center of international collaborative research partnerships with emerging countries. However, in recent years, the volume of publications produced by India has surpassed that of the United States while Bangladesh is ranked third for the strongest international collaborations. Iran and Pakistan are also emerging as major producers of research, yet publications out of these countries and India remain disproportionately restricted behind paywalls. Contamination, diarrheal disease, and water resources are the themes that characterize the majority of research on water and health. These findings may be used to accelerate equitable, inclusive research in the realm of water and health, thereby enabling gaps in global drinking water inequalities to be filled. HIGHLIGHTS: A global overview of published literature on water and health in low and lower-middle-income countries using bibliometric data Critical insights into research gaps pertaining to the literature on water and health May inform future research priorities, facilitate collaboration, and identify where national research systems must be strengthened Graphical Abstract